Thermal Characterization and Flammability of Structural Epoxy Adhesive and Carbon/Epoxy Composite with Environmental and Chemical Degradation - Campbell, Richard A.; Pickett, Brent M.; Saponara, Valeria La; Dierdorf, Douglas (Journal of adhesion science and technology, 2012)
This study investigates the thermal degradation and flammability properties of structural epoxy adhesive and carbon/epoxy composite subject to environmental and chemical agents typical of aerospace operations: water, jet fuel, hydraulic fluid, fuel additive (not mixed in jet fuel), at three conditioning temperatures similar to those experienced by an aerospace composite structure during its operation. Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) gave results consistent with those from hardness tests on control and conditioned specimens: they provide evidence for the severity of the adhesive's degradation due to hydraulic fluid (for conditioning temperatures higher than room temperature) or fuel additive (at all temperatures of this study). TGA scans show the thermal degradation of carbon/epoxy composite by fuel additive at room temperature. Through Microscale Combustion Calorimetry (MCC), the flammability properties of selected specimens were measured. Results for the treatment at room temperature confirmed those from the TGA, DSC and hardness tests. The MCC showed a decreased heat release rate for the adhesive samples treated at high temperature in hydraulic fluid and fuel additive. This may be possibly due to the increased amount of char compared to the room temperature treatments. These new results raise concerns regarding the durability of structural epoxy adhesive contaminated by hydraulic fluid or fuel additive, under simplified test conditions (no prior mechanical damage, no coatings/sealants, no mixing of fluids).